Image compression using learned dictionaries by RLS-DLA and compared with K-SVD - Skretting, Karl; Engan, Kjersti (2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
The recently presented recursive least squares dictionary learning algorithm (RLS-DLA) is tested in a general image compression application. Dictionaries are learned in the pixel domain and in the 9/7 wavelet domain, and then tested in a straightforward compression scheme. Results are compared with state-of-the-art compression methods. The proposed compression scheme using RLS DLA learned dictionaries in the 9/7 wavelet domain per forms better than using dictionaries learned by other methods. The compression rate is just below the JPEG 2000 rate which is promising considering the simple entropy coding used.